THE IMPLEMENTATION OF QUANTUM TEACHING ON STUDENT’S LEARNING OUTCOMES ON THE THEME OF UNIVERSE - Liska Berlian; Sumayah Sumayah; Lukman Nulhakim; Fitria Ramadhani (JURNAL PENA SAINS, 2022)
This study aims to determine the influence of the Quantum teaching-learning model on the learning outcomes of class VII students on the theme of the Universe. The type of this research is Quasy Experiment with Nonequivalent Control Group Design. The research population is all students of class VII SMPN 13 Serang city. The sampling technique used was purposive sampling, which selected class VII G as the control class with Discovery learning and VII H as the experimental class with the Quantum teaching-learning model. Data was collected using a test technique in the form of pretest-posttest to measure cognitive learning outcomes and non-test in a questionnaire to measure affective learning outcomes and observation sheets to measure psychomotor learning outcomes. The collected data were analyzed using a t-test at a significance level of 0.05. The results showed an influence of the Quantum teaching-learning model on the learning outcomes of class VII students at SMPN 13 Serang city. In the control class, the average value of students' cognitive learning outcomes is 45 in the significantly less category, the percentage value of students' effective learning outcomes is 71% in the excellent category, and the percentage value of students' psychomotor learning outcomes is 56% in the less category. In experiment class, the average value of students' cognitive learning outcomes is 55 in the less category, the percentage value of students' effective learning outcomes is 79% in the excellent category, and the percentage value of students' psychomotor learning outcomes is 82% in the perfect category. Finally, the Quantum teaching-learning model influences the learning outcomes of class VII students.